Word Search on the "SITUK" Application Using the Levenshtein Distance Algorithm - I Gede Susrama Mas Diyasa; Kraugusteeliana; Gideon Setya Budiwitjaksono; Alfiatun Masrifah; Muhammad Rif'an Dzulqornain (Internasional Journal of Data Science, Engineering, and Anaylitics, 2021)
Integrated System for Online Competency Certification Test (SITUK) is an application used to carry out the assessment process (competency certification) at LSP (Lembaga Sertifikasi Profesional) UPN (University of Pembangunan Nasional) “Veteran” Jawa Timur, each of which is followed by approximately five hundred (500) assessments. Thus the data stored is quite a lot, so to find data using a search system. Often, errors occur in entering keywords that are not standard spelling or typos. For example, the keyword "simple," even though the default spelling is "simple." Of course, the admin will get incomplete information, and even the admin fails to get information that matches the entered keywords. To overcome the problems experienced in conducting data searches on the SITUK application, we need a string search approach method to maximize the search results. One of the algorithms used is Levenshtein which can calculate the distance of difference between two strings. Implementation of the Levenshtein algorithm on the data search system in the SITUK application has been able to overcome the problem of misspelling keywords with the mechanism of adding, inserting, and deleting characters.